Systematic approach in struggle against Heracleum Sosnowskyi with GPS mapping usage - Solomiichuk, Mykhailo; Solomiichuk , Maksym (Quarantine and plant protection, 2024)
Goal. Analysis of long-term data on the systematic control of Heracleum Sosnowskyi on the territory of the city of Chernivtsi and the city of Kovel, taking into account the effectiveness of the use of GPS mapping. Methods. Researches conducted by visual method for identifying Heracleum Sosnowskyi in investigated regions. Used the quantity method used for determining sowing weediness. This method is based upon the weeds accounting on recording area. The spreading map formed with help of licensed software in studied districts. The device GPS-navigator used for (Garmin eTrex Legend) used for fixed points of Heracleum Sosnowskyi, areas of weeds’ hearths, spreading scopes and elimination areas, reference to coordinate system. Results. Studies conducted as per operation maps. They had been developed upon the GPS mapping. They had been formed during 2016—2022 for previous areas Heracleum Sosnowskyi control. The patented way of struggle against Heracleum Sosnowskyi tested. The way based upon the biodestructor usage after cutting for plants drying and seeds material elimination. It may be used against young plants in chemicals in the form of a complex of herbicides are also. Monitoring of the territory of the city of Chernivtsi showed that as a result of the systematic destruction of Heracleum Sosnowskyi, 12 foci of weed disappeared. The plants’ density seriously decreased from 47.8 and 43.5 plants on 1 m2 to 1.1 and 0.2 plants on 1 m2. Conclusions. Factual survey in town Chernivtsi showed that the systematic approach in struggle with Heracleum Sosnowskyi had allowed to decrease occupied area son 20 ha. The number of Heracleum Sosnowskyi plants decreased in more than 25 times. According to the results of systematic work in the city of Kovel, it is possible to claim the complete destruction of 2 outbreaks with a total area of 0.43 ha. GPS mapping usage allowed to increase monitoring and clear control for areas change of controlled object.